ANALISIS MAKNA KONJUNGSI SONOUE DAN SHIKAMO SEBAGAI SINONIM DALAM BAHASA JEPANG - Lina Rosliana (KIRYOKU, 2018)
(Title: Conjunction Shikamo and Sonoue as a Synonym in Japanese Linguistics) Japanese words have more synonyms than Indonesian words. For example, to say 'increase' in Japanese, we can use fueru (増える), masu (増す), and zouka suru (増加する). Similarly, other words, which in Indonesian equally mean 'bertanya', Japanese has kiku (聞く) and tazuneru (尋ねる). Such synonymous words often make it difficult for the Japanese learner to use them in a sentence, either written or oral, so the analysis of the meaning of synonymous words becomes an important thing in order for conforming the word we choose to the intention we want to convey . This research will discuss conjunctions sonoue (そのうえ) and shikamo (しかも) as synonyms, both of which can be paired with 'selain itu' in Indonesian. This study will be described with explanation pf every meaning that both conjunctions have, as well as similarities and differences in terms of meaning and usage. The method used is an analytic descriptive method. The object of this research is Japanese sentences that use sonoue and shikamo conjunctions, and a case study of both conjunctions.Keywords :conjunction, sonoue, shikamo, synonym